Wood fibers are a crucial microhabitat for cellulose- and xylan- degrading bacteria in the hindgut of the wood-feeding beetle Odontotaenius disjunctus - Schwarz, Melbert; Beza-Beza, Cristian F.; Mikaelyan, Aram (Frontiers in Microbiology, 2023)
Wood digestion in insects relies on the maintenance of a mosaic of numerous microhabitats, each colonized by distinct microbiomes. Understanding the division of digestive labor between these microhabitat-associated microbiomes is central to understanding the physiology and evolution of symbiotic wood digestion. A microhabitat that has emerged to be of direct relevance to the process of lignocellulose digestion is the surface of ingested plant material. Wood particles in the guts of some termites are colonized by a specialized bacterial fiber-digesting microbiome, but whether this represents a widespread strategy among insect lineages that have independently evolved wood-feeding remains an open question. Here, we investigated the bacterial communities specifically associated with wood fibers in the gut of the passalid beetle Odontotaenius disjunctus, uncovering their critical contribution to the wood digestion process. Assays of enzyme activity demonstrate that the anterior hindgut, which houses a majority of the bacterial load, is an important site for lignocellulose digestion. Wood particles enriched from the anterior hindgut contribute to a large proportion of the total enzyme activity. Short-read and long-read amplicon sequencing of the 16S rRNA gene revealed that, like termites, O. disjunctus harbors a distinct fiber-associated microbiome. However, unlike termites, this community is selectively enriched in insect-specific clades of Lactococcus and Turicibacter. Our results show that termites and passalids appear to have independently evolved strikingly similar symbiotic solutions to thrive on their challenging diet, but have done so by recruiting distinct fiber-digesting symbionts.